Measuring and Ranking the Physical Resilience of Urban Areas Against Earthquakes: A Case Study of the Metropolis of Tabriz - yaser nazaryan; amane haghzad; laila ebrahimi; Kia bozorgmehr (تحقیقات کاربردی علوم جغرافیایی)
Urbanization and the increase in urban populations, resulting from both natural population growth and rural-to-urban migration, have led to the concentration of significant material and spiritual human capital within urban settlements. Concurrently, various natural and human-induced crises pose threats to these capitals. Urban management has initiated a range of programs to address these crises, with a contemporary focus on enhancing the resilience of cities. The concept of resilience can be examined across various dimensions, including physical, economic, social, and environmental aspects. The present study adopts a descriptive-analytical approach with the objective of assessing the physical resilience of metropolitan areas in Tabriz and determining their status relative to one another. To achieve this goal, multi-criteria decision-making methods (MADM) and the Analytic Hierarchy Process (AHP) have been employed. Additionally, three models—Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), VIKOR, and Complex Proportional Assessment (COPRAS)—have been utilized to rank the regions in terms of physical resilience. Ultimately, the Copeland model was applied to integrate the results from the aforementioned models. The findings indicate that regions 2, 8, and 9 collectively exhibit the highest levels of physical resilience, followed by regions 1, 10, 3, 7, 5, 4, and, lastly, region 6, respectively.